Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat pada Kantor Desa Suatang Keteban Kecamatan Paser Belengkong Kabupaten Paser - Ibnu Khayath Farisanu; Indri Farradina; Erny Noer Herliana (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The aim of this research is to determine the influence of service quality on community satisfaction at the Suatang Keteban Village Office, Paser Belengkong District, Paser Regency. From the results obtained, the validity test of 26 statements was declared valid because the value of rcount > rtable. The results of the Cronbach Alpha standard reliability test are greater than 0.6 (0.928 > 0.6), so it is stated that each item of the statement and the level of consistency are good, so the results are acceptable. From the results of data analysis and data tabulation, it can be seen that the results of the regression equation are Y = -1, 414 + 0.855 means that the relationship between public satisfaction and the variables Direct Evidence (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), Empathy (X5) is very strong. From the results of the Adjusted R Square of 0.612 or 61.2%, this means that the independent variables namely Direct Evidence (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), Empathy (X5) provide the percentage of contributions that affecting the dependent variable, namely Community Satisfaction (Y) at the Suatang Keteban Village Office, Paser Belengkong District, Paser Regency, amounting to 61.2%, while the remaining 38.8% was influenced by other variables not studied. The results of the F test calculation analysis (simultaneous) obtained an Fcount value of 16.482 and Ftable using a significance level of 0.000 while the Ftable value was 2.43. So Fcount is 16.482 > Ftable value is 2.43 and the hypothesis test is accepted because there is a significant influence on community satisfaction. The results of the t test calculation analysis show that the t value of the Direct Evidence variable (X1) is 4.343 with a significant probability of 0.000, Responsiveness (X3) is 3.867 with a significant probability of 0.000, and Guarantee (X4) is 3.099 with a significant probability of 0.003 which has an influence on Satisfaction Society (Y). Meanwhile, the t-calculated value of Reliability (X2) is -1.445 with a significant probability of 0.155, Empathy (X5) is -1.681 with a significant probability of 0.100, it has no effect on Community Satisfaction (Y). Based on the SPSS results, the Direct Evidence variable (X1) has a dominant influence on Community Satisfaction (Y) with the highest t-count value of 4.343 with a significant rate of 0.000 at the Suatang Keteban Village Office, Paser Belengkong District, Paser Regency, thus the second hypothesis in Chapter II is not proven which states that the empathy variable has a dominant influence or H0 is accepted and Ha is rejected.